The Bio-herbicidal potential of some wild plants with allelopathic effects from Tabuk Region on selected local weed species - Alanaz, Amjad R.; Alatawi, Eman A. S.; Alotaibi, Rahaf S.; Alatawi, Eman A. H.; Albalawi, Attaf D.; Alhumayri, Hadeel A.; Alatawi, Qasem S.; Alharbi, Basmah M. (Frontiers in Plant Science, 2023)
Weeds are considered one of the most serious problems limiting global agricultural production. As a result, chemical herbicides have been extensively used for weed control. However, overuse of synthetic herbicides, has resulted in public concerns over the effect of herbicides on the health of the ecosystems and humans. In the food system, innovative approaches are needed to foster sustainable practices that preserve biodiversity, conserve habitats, and mitigate climate change factors. Thus, alternatives are required to control the weeds. This study aimed to determine the impact of some wild plants’ (Citrullus colocynthis, Euphorbia retusa, Retama raetam, Artemisia monosperma, Tamarix gallica, and Artemisia judaica) allelopathic potentials (at rates of 0, 15, 25, 35, and 50 g/L) on seed germination of selected local weeds (Portulaca oleracea, Amaranthus retroflexus, and Chloris barbata) collected from different locations in Tabuk region, Saudi Arabia. GC-MS analysis was used to evaluated the main compounds in the wild plants under study. The experimental design was completely randomized block design (CRBD) with three replicates. According to the results, phytochemical screening of the wild plants using GC-MS analysis showed a wide range of phytochemicals. Amaranthus retroflexus exhibited the highest germination rate in the control group. In addition, applying 5 g/L and 20 g/L of Citrullus colocynthis extracts had no discernible effect on the rate of germination of A. retroflexus seed; however, they were able to reduce the germination rate as compared to the control. As the extract concentration of Artemisia monosperma rose to 20 g/L, the germination rate of A. retroflexus dropped. Neither 35 g L-1 nor 50 g L-1 of A. monosperma extract inhibited the germinate of A. retroflexus. The germination rate of Portulaca oleracea decreased with increasing extract concentration of C. colocynthis. The extract of C. colocynthis at 50 g/L had the lowest rate. The germination rate of Chloris barbata decreased with increasing extract concentration of C. colocynthis. The highest germination rate of C. barbata was observed in control, followed by 5g/L, while no germination was observed at 20, 35, and 50 g/L of C. colocynthis extracts. A. retroflexus’s root length shrank when the extract concentration of C. colocynthis rose. A. retroflexus’s control sample had the most extended root length, followed by 5 and 20 g/L, respectively. C. colocynthis at 35 and 50 g/L showed no root elongation as this treatment inhibited radicle protrusion. High concentration of d-Glycero-d-galacto-heptose and pentane in C. colocynthis aqueous extract may be the cause of C. colocynthis’ ability to inhibit Chloris barbata germination. The entire C. barbata plant length decreased when treated with 5 g/L of C. colocynthis extract. No growth was seen at any of the higher C. colocynthis concentrations (20, 35, and 50 g/L). The present work revealed that cultivating allelopathic crops like the selected studied wild plants from the Tabuk region has a promising future as an antagonistic species in a biological weed control program or combined with integrated weed management in agricultural food production.